Trust in the Electric Vehicle Service Ecosystem as a Determining Factor for Consumer Purchase Intent: A Systematic Literature Review - Panji Asmara, Dimas (Journal Research of Social Science, Economics, and Management, 2026)
This study presents a systematic literature review to analyze consumer trust in the electric vehicle ecosystem as a significant predictor of purchase intention. The review methodology involves aggregating and synthesizing relevant studies from leading academic databases to identify key factors shaping such perceptions of trust. The analysis focuses on aspects of charging infrastructure, after-sales service availability, and government policy support that collectively influence consumer confidence in the functionality and sustainability of electric vehicles. This research will identify knowledge gaps and provide comprehensive insights for policymakers, automotive manufacturers, and future researchers to understand the dynamics of electric vehicle adoption.